Identification of candidate genes involved in the etiology of sporadic Tourette syndrome by exome sequencing. Issue 7 (13th June 2017) - Eriguchi, Yosuke; Kuwabara, Hitoshi; Inai, Aya; Kawakubo, Yuki; Nishimura, Fumichika; Kakiuchi, Chihiro; Tochigi, Mamoru; Ohashi, Jun; Aoki, Naoto; Kato, Kayoko; Ishiura, Hiroyuki; Mitsui, Jun; et al.
Abstract : Tourette Syndrome (TS) is a neurodevelopmental disorder characterized by chronic motor and vocal tics. Although there is a large genetic contribution, the genetic architecture of TS remains unclear. Exome sequencing has successfully revealed the contribution of de novo mutations in sporadic cases with neuropsychiatric disorders such as autism and schizophrenia. Here, using exome sequencing, we investigated de novo mutations in individuals with sporadic TS to identify novel risk loci and elucidate the genetic background of TS. Exome analysis was conducted for sporadic TS cases: nine trio families and one quartet family with concordant twins were investigated. Missense mutations were evaluated using functional prediction algorithms, and their population frequencies were calculated based on three public databases. Gene expression patterns in the brain were analyzed using the BrainSpan Developmental Transcriptome. Thirty de novo mutations, including four synonymous and four missense mutations, were identified. Among the missense mutations, one in the rapamycin‐insensitive companion of mammalian target of rapamycin ( RICTOR )‐coding gene (rs140964083: G > A, found in one proband) was predicted to be hazardous. In the three public databases analyzed, variants in the same SNP locus were absent, and variants in the same gene were either absent or present at an extremely low frequency (3/5, 008), indicating the rarity of hazardous RICTOR mutations in the general population. The de novo variant of RICTOR may be implicated in the development of sporadic TS, and RICTOR is a novel candidate factor for TS etiology.